A A Case Report of Hamartomatous Bifid Tongue: A Rare Congenital Anomaly - Walid, Adnan; Shafayat Chowdhury, Tameem; Farhad, Tanzil; Sharmin, Effat; Das, Utpak; Sen, Showrov; Afrin, Shaila; Barua, Shuvramoy; Redwan Chowdhury, Mymoon (Iranian Journal of Pediatric Surgery, 2024)
Congenital bifid tongue is a rare malformation, which is usually present in association with other oral findings such as cleft palate and tongue mass. The authors have found a rare case of congenital bifid tongue together with absence of lingual frenulum, and a hamartomas mass in a 9-month-old female infant. Mother complains of difficulties in sucking breast milk and dribbling milk during breast feeding, as well as some episodes of positional dyspnea and choking with cyanosis during feeding. The mass was excised, along with an excess portion of the left tongue, and the bifid tongue was surgically repaired in layers after excision. The histopathological report was used to confirm the diagnosis of hamartoma. The review of literature, description of the lesion, diagnosis, and management of this finding are all outlined.